2022
DOI: 10.3748/wjg.v28.i4.464
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DEAD-box 51 inhibits tumor growth of esophageal squamous cell carcinoma via the PI3K/AKT pathway

Abstract: BACKGROUND Esophageal squamous cell carcinoma (ESCC) is one of the most prevalent malignancies that seriously threaten people’s health worldwide. DEAD-box helicase 51 (DDX51) is a member of the DEAD-box (DDX) RNA helicase family, and drives or inhibits tumor progression in multiple cancer types. AIM To determine whether DDX51 affects the biological behavior of ESCC. METHODS The expression of DDX51 in ESCC tumor tissues and adjacent normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The PI3K/AKT signaling pathway is frequently activated in a variety of tumors and plays a crucial role in tumor cell proliferation, apoptosis, metastasis, and other malignant behaviors [ 38 42 ]. It has been found that IL-1β facilitates the expression of vasculogenic mimicry markers in breast cancer cells by activating the PI3K / Akt signaling pathway, exerting adverse effects on tumor angiogenesis and cancer cell invasion and metastasis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway is frequently activated in a variety of tumors and plays a crucial role in tumor cell proliferation, apoptosis, metastasis, and other malignant behaviors [ 38 42 ]. It has been found that IL-1β facilitates the expression of vasculogenic mimicry markers in breast cancer cells by activating the PI3K / Akt signaling pathway, exerting adverse effects on tumor angiogenesis and cancer cell invasion and metastasis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K / AKT pathway is frequently over-activated in various tumor types [ 26 ]. Several current studies [ 27 31 ] showed that the PI3K / AKT pathway can promote ESCC cell growth and metastasis, and the phosphorylation level of both was significantly and positively correlated with the invasion and metastatic ability of cancer cells. This is in line with our finding that PLCD3 downregulation led to a significant reduction in PI3K / AKT phosphorylation, versus PLCD3 upregulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that DDX members are dysregulated in multiple cancers and function as key players in tumor progression [ 30 ]. Hu et al identified that DDX51 regulates cellular proliferation in esophageal squamous cell carcinoma through the PI3K/AKT/mTOR pathway [ 31 ]. Jiang et al proved that knock-down of DDX46 caused a significant reduction in cell invasion and migration in osteosarcoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%